Fashion and sustainability: what future professional designers think (ModaPalavra e-periódico, 2019)
ThisqualitativeresearchaimedtoascertainthesustainabilityknowledgeacademicstudentsofaFashiondesigncoursepossessed.Thefirstresearchercollecteddataduringapedagogicalintervention,withinthecontextoftheproductdevelopmentdiscipline.Twentythird-yearstudentsfromtheabove-mentionedcourseparticipatedintheresearchandmobilizedtorespondtoaquestionnaire,presentseminarsandproducetextsaboutsustainability.Thedataanalysis,collectedthroughaquestionnaire,theseminarsvideosandwrittentexts,showedthatthestudents,inadditiontoincreasingtheirunderstandingaboutsustainability,reflectedonitsimportanceinthefieldoffashion,futureworkareaoftheresearchedstudents
Keywords: fashion designer; environmental education; sustainability